Enhancement of elastic wave energy harvesting using adaptive piezo-lens. (1st September 2017) - Yi, K.; Collet, M.; Chesne, S.; Monteil, M.
Highlights: The piezo-lens can focus waves and the focal point is tunable. The output power is improved when harvesting from the focused waves. The harvesting system incorporating the piezo-lens is adaptable to environment changes. Abstract: This paper exploits an adaptive piezo-lens to improve the harvested power (energy) from traveling waves. The piezo-lens comprises a host plate and piezoelectric patches bonded on the plate surfaces. The piezoelectric patches are shunted with negative capacitance (NC) circuits. The spatial variation of the refractive index inside the piezo-lens domain is designed to fulfill a hyperbolic secant function by tuning the NC values. This design allows the piezo-lens to continuously bend the incident waves toward a designed focal point, resulting in an energy concentration zone with a high level of energy density. This energy concentration effect may be exploited to improve the harvested power from waves. In addition, the piezo-lens is tunable - the waves can be focused at different locations by designing the NC values. This tunability may make the harvesting systems incorporating a piezo-lens be adaptable to environment changes. The above expected practical interests of the piezo-lens for wave energy harvesting are discussed and verified in the paper. Fully coupled numerical models are developed to predict the dynamical responses of the piezoelectric systems.